Perineal Body Length and Pelvic Organ Prolapse in Menopausal Women: Panjang Perineal Body dan Prolaps Organ Panggul pada Wanita Menopause - Chairun Nisa; David Lotisna; Deviana S. Riu; St. Maisuri T. Chalid (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective: To determine the correlation between the perineal body length and the pelvic organ prolapse (POP) in menopausal women. Methods: The total vaginal length (TVL), genital hiatus (GH), and perineal body (PB) length as the POP-Q component were measured at 60 menopausal women enrolled in a cross-sectional study. Results: Menopausal women with POP have the shorter perineal body (63.3%; <3 cm) compared with menopausal women without POP (36.7%; ≥3 cm). The mean length of the perineal body in menopausal women who suffer POP 2.81 ± 0.26 cm while in women without POP is 3.23±0.17 cm. POP risk was 25 times in menopausal women with a perineal body length <3 cm compared with longer perineal body (p = 0.01; OR = 25.4; 95% CI 3.1-209.1).Conclusion: Perineal body length is a risk factor for pelvic organ prolapse in menopausal women.Keywords: perineal body, prolapse, pelvic organ prolapsed Abstrak Tujuan: Menentukan korelasi panjang perineal body dengan kejadian prolaps organ panggul (POP) pada perempuan menopause. Metode: Pengukuran komponen POP-Q meliputi total vaginal length (TVL), genital hiatus (GH), dan panjang perineal body (PB) dilakukan pada 60 perempuan menopause yang dilibatkan dalam penelitian potong lintang. Hasil: Perempuan menopause dengan POP memiliki perineal body yang lebih pendek (63,3%; <3 cm) dibandingkan dengan perempuan menopause tanpa POP (36,7%; ≥3 cm). Panjang rata-rata perineal body pada perempuan menopasue yang menderita POP 2,81 ± 0,26 cm sedangkan pada perempuan tanpa POP adalah 3,23 ± 0,17 cm. Risiko POP 25 kali pada perempuan menopause dengan panjang perineal body <3 cm dibandingkan dengan tubuh perineum yang lebih panjang (p = 0,01; OR = 25,4; 95% CI 3,1-209,1). Kesimpulan: Panjang perineal body merupakan faktor risiko prolaps organ panggul pada perempuan menopause. Kata kunci : perineal body, prolapsed, prolaps organ panggul